Implementasi Komunikasi Verbal dan Non Verbal Dalam Proses Menghafal Doa Sehari-Hari pada Anak Usia Dini di Program Anak Sholeh di Masjid Istiqomah Sekip, Kec Sibiru-Biru Kab. Deli Serdang - Khoirunnisa Az–Zahra.T; Fatma Yulia (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The study's objective is to determine whether humans use communication as a transformational tool. can communicate his desires with other people. Correspondence completed in the retention cycle will constantly utilize verbal correspondence by talking or composing while non-verbal correspondence utilizes images and body developments (signals). It turned out that an ustazah's implementation of memorizing daily prayers through verbal and nonverbal communication had significant effects for early childhood. There is an expansion in interest and higher appeal in taking part in the remembrance cycle on the grounds that the ustazah can make a fascinating environment. In addition, this study employed descriptive qualitative methods to directly observe facts, items, and certain characteristics through interviews with religious educators and program administrators and documentation. The information assortment strategy utilized was field studies Keywords: childhood communication, daily prayer